Prediction of Retinal Loss Based on Lesion of the Optic Nerve in Acute Stage of Optic-Neuritis - Abdul Ghafoor Magsi, Zuhaib Ahmed Soomro, Deepak Kumar, Lal Chand Dhingra, Ishfaque Ahmed Simair, Najam-Us-Saqib Ansari, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To assess the predictive features of optic neuritis in retinal loss through optic nerve lesion identification. Study design: Prospectively longitudinal study Place and duration of study: Ghulam Muhammad Mahar Medical College Sukkur and Shaheed Mohtarma Benazir Bhutto Medical University Larkana from 1st January 2021 to 30th June 2022. Methodology: One hundred and ten patients suffering from acute optic neuritis ≤8 weeks were enrolled. Retinal optical-coherence tomography was performed in all patients. Fifty five patients in the whole cohort while clinically isolated syndrome (CIS) 25 patients and relapsing remitting multiple sclerosis (RRMS) as well as neuromyelitis-optica spectrum disorders (NMOSD) and isolated optic neuritis as 20, 3 and 7 respectively. Brain optic nerve magnetic resonance imaging which included three-dimensional double inversion recovery sequence was also conducted at acute phase (M0) and then post 12 months (M12). Results: The mean age of the cases was 30.85±8.9 years. There was a higher frequency of males then females. The duration of the disease was found highest in RRMS cases with 50.31±77.45 months. The variance in estimated and standard error of the ganglion cell-inner plexiform layer volume change was significantly different in whole acute optic neuritis cases as well as the one with CIS and multiple sclerosisat cohort. Conclusion: Optic nerve-lesion length in prediction of retinal-neuroaxonal loss in cases of optic neuritis. The optic-nerve lesion length can also be considered as a biomarker for the process of retinal remodeling as well as visual impairment. Key words: Optic nerve lesion, Acute phase, Optic neuritis (ON), Retinal neuronal loss